Psychiatric Visum Et Repertum as A Method of Examining Victims of Domestic Violence - Siti Purwanti; Achmad Miftah Farid; Muhammad Amin Hanafi (Universitas Muhammadiyah Surakarta, 2025)
This study discusses the settlement of criminal cases of psychological violence in the household through the psychiatric visum et repertum method. Psychological violence is often not physically visible, but its impact is profound on the mental and emotional state of the victim. The formulation of the problem in this study is what is the legal basis that supports the use of psychiatric visum et repertum in the criminal justice system in Indonesia and what is the role of psychiatric visum et repertum as evidence in cases of psychological violence in the household. Using normative research methods, this study analyzes laws and regulations in the context of law implementation in Indonesia. This research is expected to contribute to the reform of the criminal justice system by prioritizing a humane approach, based on Pancasila values, and providing practical guidance for law enforcement in handling cases of psychological violence. Thus, this study aims to understand the role of the psychiatric visum et repertum method as legal evidence in cases of psychological violence and explore the legal basis for its application in Indonesia.